PENGARUH CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR PERTAMBANGAN Riset Empiris pada Perusahaan Sektor Pertambangan yang terdaftar di Bursa Efek Indonesia Tahun 2010-2012 - , EVI NOER ENDAH, Taufikur Rahman, S.E., M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed to examine the influence of corporate governance and corporate social responsibility on financial performance. The corporate governance is represented with audit committee educational background, managerial ownership, institutional ownership, foreign ownership, ownership concentration, and minority interest disclosure and also firm size and sales growth as control variables. The sample used in this study consists of Indonesia Stock Exchange (IDX)-listed companies from mining sector in 2010-2012. Purposive sampling method used in the selection of the data sample and resulted 81 samples. This research uses linear regression analysis. The result of this study shows that only corporate governance have significant influence on financial performance.